Randomised controlled trial of long term portographic follow up versus variceal band ligation following transjugular intrahepatic portosystemic stent shunt for preventing oesophageal variceal rebleeding. Issue 3 (11th February 2004) - Tripathi, D; Lui, H F; Helmy, A; Dabos, K; Forrest, E; Stanley, A J; Jalan, R; Redhead, D N; Hayes, P C
Abstract : Background/aims: Transjugular intrahepatic portosystemic stent shunt (TIPSS) is effective in the prevention of variceal rebleeding but requires invasive portographic follow up. This randomised controlled trial aims to test the hypothesis that combining variceal band ligation (VBL) with TIPSS can obviate the need for long term TIPSS surveillance without compromising clinical efficacy, and can reduce the incidence of hepatic encephalopathy. Patients/methods: Patients who required TIPSS for the prevention of oesophageal variceal rebleeding were randomised to either TIPSS alone (n = 39, group 1) or TIPSS plus VBL (n = 40, group 2). In group 1, patients underwent long term TIPSS angiographic surveillance. In group 2, patients entered a banding programme with TIPSS surveillance only continued for up to one year. Results: There was a tendency to higher variceal rebleeding in group 2 although this did not reach statistical significance (8% v 15%; relative hazard 0.58; 95% confidence interval (CI) 0.15–2.33; p = 0.440). Mortality (47% v 40%; relative hazard 1.31; 95% CI 0.66–2.61; p = 0.434) was similar in the two groups. Hepatic encephalopathy was significantly less in group 2 (20% v 39%; relative hazard 2.63; 95% CI 1.11–6.25; p = 0.023). Hepatic encephalopathy was not statistically different after correcting for sex and portal pressure gradient (p = 0.136). Conclusions: TIPSS plus VBL without long term surveillance is effective in preventing oesophageal variceal rebleeding, and has the potential for low rates of encephalopathy. Therefore, VBL with short term TIPSS surveillance is a suitable alternative to long term TIPSS surveillance in the prevention of oesophageal variceal rebleeding.